Choujin X. Volume 11 - Ishida, Sui (Viz signature., 2026)
Best friends Tokio and Azuma do everything together, even if most of the time it feels like Tokio is just stumbling along in Azuma's cooler, more talented footsteps. But when they're attacked one night by a superhuman mutant called a choujin, Tokio finally has a chance to shine--by turning into a choujin himself! The assault on the Tower of Mourning has begun. After breaching the tower defenses by air, Tokio and the rest of the Yamato Mori forces begin their infiltration of the upper levels. But despite all their careful strategies and precautions, no one is ready when the tower itself is turned against them! Can Tokio and the scattered, disoriented Yamato Mori troops pull it together in time to face the monstrous choujin of the tower?